Religion, Loneliness, and Mental Health: A Case Study of Undergraduate Well-Being at a Jesuit University - Tricia M. Ross; Theodore G. Dedon; Christopher Krall; Amy S. Badura-Brack (Journal of Religion & Society Supplement Series, 2026)
This study examines loneliness, belonging, mental health, religious practice and well-being among undergraduate students at a Midwestern Jesuit university. Survey data from 1,286 students showed lower overall loneliness than national averages, but significant differences across religious and spiritual identities. Students identifying as religious or spiritual reported lower loneliness, stronger social fit, and greater belonging than peers who were uncertain, unaffiliated, or non-spiritual. Religious well-being was positively associated with self-acceptance, personal growth, positive relationships, adaptive coping, and lower depressive symptoms. Both religious practice and religious well-being were associated with adaptive coping. The findings suggest that loneliness among undergraduates in emerging adulthood is shaped by a multitude of factors including religious well-being, institutional context, and belonging within campus life. As a case study, Creighton highlights how colleges and universities may address loneliness through attention to social fit, inclusion, and the structures of community that support student well-being and belonging.